Metabolic syndrome and pharmacotherapy outcomes in patients with type 2 diabetes mellitus - Alawdi, Shawqi H.; Al-Dholae, Mohammed; Al-Shawky, Salah (Frontiers in Clinical Diabetes and Healthcare, 2024)
BackgroundMetabolic syndrome is a group of metabolic abnormalities that increase predisposition to several diseases including ischemic heart disease and diabetes mellitus. The study aimed to investigate metabolic syndrome among patients with type-2 diabetes mellitus (DM), and its impact on pharmacotherapy outcomes.MethodsAn observational cross-sectional study was performed on 910 patients with type-2 DM between June and December 2023. Fasting blood sugar, triglycerides, high-density lipoproteins (HDL), blood pressure, and abdominal obesity were measured. Metabolic syndrome was identified according to the National Cholesterol Education Program Adult Treatment Panel III criteria. Pharmacotherapy outcomes were assessed according to American Association of Clinical Endocrinologists and American Diabetes Association guidelines using the ability to achieve adequate glycemic control and normal levels of blood pressure and fasting plasma lipoproteins.ResultsIn total, 87.5% of type-2 DM patients had metabolic syndrome; the prevalence increased with age and was higher among females. Metabolic syndrome showed the following distribution of risk factors: insulin resistance (100%), low HDL (95.3%), elevated blood pressure (83%), triglycerides dyslipidemia (80.1%), and abdominal obesity (62.5%). Majority of the patients had either 5 or 4 risk factors of metabolic syndrome. The most common comorbidities were dyslipidemia (97.7%) and hypertension (83%). Treatment outcomes were insufficient where adequate glycemic control was only achieved in 12% of type-2 DM patients, and proper management of comorbid dyslipidemia and hypertension was achieved in 29% and 40.9% of patients, respectively. Adequate blood pressure control was less achieved in patients with metabolic syndrome (34.4%) than those without metabolic syndrome (77.2%). Similarly, dyslipidemia was less controlled in patients with metabolic syndrome (26.9%) than in those without metabolic syndrome (47.3%).ConclusionPharmacotherapy outcomes were inadequate for most patients with type-2 diabetes mellitus. Adopting early preventive and therapeutic interventions for metabolic syndrome is advised to improve treatment outcomes of the comorbid dyslipidemia and hypertension.